Tailings dust — evolution over fifty years of gold mine tailings sources and sensitive receptors on the central Witwatersrand - Ojelede, M.E.; Liebenberg-Enslin, H.; Annegarn, H.J. (Mine Closure 2009: Proceedings of the Fourth International Conference on Mine Closure, 2009)
For over a century, gold exploration and extraction has been a continuous activity on the Witwatersrand. The high temporal and spatial dynamics often associated with mines and mining areas have seen tailings, receptors and the exposed population in this region evolve over time. With a history of dust storms which dates back to 1920s, the health and safety of neighbouring communities are potentially at risk. This paper investigates dust emissions from a tailings impoundment in central Gauteng and its subsequent dispersal to residential areas. The spatial evolution of tailings and their relationship with built-up areas is assessed using multi-temporal aerial photographs, covering four periods from 1952 to 2002. Image mosaics were generated from four different overlapping scenes for each period and geo-referenced to a vector data (1:50 000) topographic map. The 1952 acquisition, which had a 2.4 m resolution, served as reference object for the re-sampling and co-registration processes. Changed areas were digitised, assessed and analysed in a geographic information system (GIS) environment. Source emissions were estimated for the different periods. Meteorological data and source parameters, such as grain size distribution of tailings, combined with spatial and temporal changes observed, served as input for a dispersion model. Simulated ground level concentrations of dust, changes observed in tailings surface area, height, residential area and exposed population for the time series are reported. These results are important for risk assessment and landscape planning, since tailings are subject to reworking and important for planned new mining within the Gauteng mega-city region (Witwatersrand). Overall, the outcome of this study provides insight into the nature of the historical and current exposure and risks from gold mine tailings impoundments.